Application of Discovery Learning Model to Improve the Understanding Concept of High School Students on Buffer Topic - Nurfauzia Nurfauzia; Ijirana Ijirana; Suherman Suherman (Jurnal Akademika Kimia, 2021)
This study aimed to describe the increase in understanding of students in class XI SMA 7 Palu on the buffer solution material after applying the discovery learning model. This type of research was pre-experiment with the design of one group pre-test-post-test. This study was conducted in two replication classes, namely, class XI MIA 1 as replication class 1 (n = 26) and class XI MIA as replication class 2 (n = 24). Testing of the data from research results data used descriptive statistical analysis of the understanding concept. The criteria for understanding the concept was good if the percentage of students who have the category of moderate, high, and very high is not less than 60%. The data results of analysis understanding of each concept obtained in the replication class 1. The concept of buffer, score 65. 38% increased to 96.15%. The concept of the properties of the buffer score 3.84% increased to 96.15%. The concept of acid-base buffer solution, score 0% increased to 92.3%. The concept of pH acid buffer, score 0% increased to 88.46%. The concept of pH base buffer, score 0% increased to 84.61%. In replication class 2, the concept of buffer solution score is 20.83%, increased to 91.66%. The concept of acid and base buffer solution, score 12.5% increased to 91.66%. The concept of pH base buffer, score 4.16% increased to 83.33%. The results of the analysis showed that there is an increase in understanding the good concept by applying the discovery learning model in the buffer material.